Approximation of periodic functions by constants in the metric spaces $ϕp(L)$ - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using the best approximations of functions by constants, we establish necessary conditions for the moduli of continuity of periodic functions in metric spaces with integral metric and find the Young constants of these spaces.